Dinosaur who lived in my backyard (The) - Hennessy, B. G. (New York : Scholastic Inc, 1988)
There used to be a dinosaur who lived in my backyard. Sometimes I wish he still lived here. We would have lots of fun together!.
Keywords: Dinosaurs-Fiction